Ability of soluble TREM2 and PRO-C3 as biomarkers to predict changes in MASLD activity - Charlotte Wilhelmina Wernberg; Vineesh Indira Chandran; Mette Munk Lauridsen; Maria Kløjgaard Skytthe; Camilla Dalby Hansen; Johanne Kragh Hansen; Lea Ladegaard Grønkjær; Birgitte Gade Jacobsen; Tina Di Caterino; Sönke Detlefsen; Maja Thiele; Alejandro Mayorca Guiliani; et al. (JHEP Reports)
Background & Aims: Diet and weight loss remain the primary treatment for most patients with metabolic dysfunction-associated fatty liver disease (MASLD), with one recent drug therapy approved for severe cases. However, a significant need remains for non-invasive tests (NITs) that can assist clinicians in evaluating treatment response. We aimed to explore the ability of several NITs to reflect a change of at least one point in histologic non-alcoholic fatty liver disease (NAFLD) Activity Score (NAS). Methods: This study explores biomarkers reflecting treatment response in 173 patients from secondary care with type 2 diabetes or severe obesity, all of whom underwent repeated liver biopsies and blood samples. We measured soluble triggering receptor expressed on myeloid cells 2 (TREM2), collagen markers PRO-C3, PRO-C4, PRO-C6, PRO-C8, and PRO-C18L and liver stiffness measured by FibroScan, FAST-score, and homeostatic model assessment of insulin resistance (HOMA-IR). We studied biomarker changes and their capacity to reflect liver biopsy alterations in two distinct cohorts, using comparative paired analyses and multivariable logistic regression to evaluate the results. Results: Mean age was 52 years (±12), 38% male, 52% had NAS ≥3 at baseline (90/173), 70% had F0–F1 fibrosis, and 23% (39/173) had metabolic dysfunction-associated steatohepatitis. Significant differences were seen in sTREM2, PRO-C3, HOMA-IR, and FAST-score levels by NAS changes (worsened, no-change, improved) (p = 0.0001). In multivariable analysis, sTREM2 + PRO-C3 and HOMA-IR predicted NAS improvement (AUROC >0.75), with an odds ratio of 1.13 for each unit decrease (p = 0.001, 95% CI 1.04–1.21). FIB-4 and non-alcoholic fatty liver disease fibrosis score (NFS) did not reflect NAS improvement (AUROC <0.60, OR <1.05, p >0.5). Conclusions: sTREM2, PRO-C3, and HOMA-IR indicate NAS improvement and warrant further investigation as surrogate markers for gauging intervention response. Impact and implications: Non-invasive tests (NITs) will play a crucial role in monitoring treatment responses in metabolic dysfunction-associated steatotic liver disease, providing a viable alternative to liver biopsies. Our study investigates whether NITs reflect histological responses based on changes in the non-alcoholic fatty liver disease (NAFLD) activity score (NAS) in patients with type 2 diabetes mellitus or obesity. We used non-invasive markers, some corresponding to different biological aspects of disease severity. We found that reductions in certain NIT levels correlate well with NAS reduction and composite histological improvements (lobular inflammation and ballooning). Combining soluble triggering receptor expressed on myeloid cells 2, PRO-C3, or homeostatic model assessment of insulin resistance enhances the potential for monitoring NAS improvement. Clinical Trials Registration: ClinicalTrials.gov (NCT03068078; NCT03535142).